Perancangan Modul Pendukung Keputusan Klinis Dalam Peresepan - Naibaho, Yosep Parlindungan; Chrisantyo, Lukas; Lukito, Yuan (Fakultas Teknologi Informasi, 2023)
The manual prescription process has a potential of error, which can lead to undesirable consequences, particularly for patients. As the advancement of technology, the use of decision support systems is necessary to minimize errors in prescription delivery. In this study, a decision support system module will be developed to assist prescription process by transferring knowledge possessed by experts as the knowledge base of the system. This module will use rule-based method as the decision-making method by applying validated rules based on the acquired knowledge base. To test the accuracy of the module’s output, test case design will be used as the method. The result of the research showed that all tested scenarios have the same results as the expected results, indicating that the use of rule-based expert system us effective in developing this decision support module. However, the module can still be improved by adding more data as the knowledge base or integrating the module directly with existing system in clinic or hospital.